African American artists and the New Deal art programs : opportunity, access, and community - Calo, Mary Ann, 1949- (The Pennsylvania State University Press, 2023)
"Examines the involvement of African Americans in the New Deal art programs, shifting emphasis from individual artists toward broader issues informed by the uniqueness of Black experience"--